Light-Emitting Diodes and Photodetectors Advances and Future Directions - Casalino, Maurizio; Thirumalai, Jagannathan (IntechOpen, 2021)
This book provides a detailed overview of the most recent advances in the fascinating world of light-emitting diodes (LEDs), organic light-emitting diodes (OLEDs), and photodetectors (PDs). Chapters in Section 1 discuss the different types and designs of LEDs/OLEDs and their use in light output, color rendering, and more. Chapters in Section 2 examine innovative structures, emerging materials, and physical effects of PDs. This book is a useful resource for students and scientists working in the field of photonics and advanced technologies.